THE INFLUENCE OF PERFORMANCE APPRAISAL AND MOTIVATION ON JOB SATISFACTION IN THE REDUCTION TEAM OF PT INDONESIA ASAHAN ALUMINIUM (INALUM) - Septian Arrisandi; Erie Priyandha; Rusmewahni; Limega Candrasa (RADJA PUBLIKA, 2025)
Abstract This study aims to determine the effect of performance appraisal and motivation on job satisfaction in the A team of the reduction section of PT Indonesia Asahan Aluminium (Inalum). In this study, 60 employees were used using census or total sampling techniques. The data collection technique was carried out by distributing questionnaires to respondents using a Likert scale measurement scale. The data that has been collected is then processed with the SPSS 25.00 application by conducting validity and reliability tests on the research instrument. Furthermore, normality, multicollinearity and heteroscedasticity tests were carried out. Then multiple linear regression analysis tests were carried out and for hypothesis testing using partial tests (t) and simultaneous tests (F). Based on the results of hypothesis testing, it is found that performance appraisal has no effect on job satisfaction, motivation affects job satisfaction and performance appraisal and motivation have a joint effect (simultaneously) on job satisfaction.